Guidance problems of students in the Sekolah Guru A/Sekolah Guru Taman Kanak-kanak Negeri of Salatiga (Indonesia) - Susilaradeya, R. Dulkaidja 1927- (s.n.], 1965)
This paper identifies common problems of the students in the Sekolah Guru A/ Sekolah Guru Taman Kanak-Kanak Negeri of Salatiga. The problem checklist data reveal that all the subjects of this study have had reported problems in school. The problem areas indicated (in the order of most to least frequent) are: school, leisure time, personality, social, home, religion, and health.